Ժամանակակից հայերենի ստորոգյալի բաղադրիչների շարադասությունը - Ասիլբեկյան, Շուշան
Цель статьи — рассмотрение расположения компонентов глагольных и именных сказуемых аналитической конструкции в современном армянском языке.В статье приводятся основные модели расположения компонентов в различных типах сказуемого и разъясняется структурно-семантическая обусловленность прямого порядка и инверсии в аналитических конструкциях сказуемого. The purpose of the article is to arrange the components of verbal and nominal predicates of an analytical construction in modern Armenian language.In the article the basic models of arranging the components in different types of predicate are examined and also the structural-semantic construction of the direct order and inversion in analytical construction of a predicate is explained.
Keywords: Լեզվաբանություն